WAYS TO APPROACH THE AUTEUR THEATRE - Koecher-Hensel, Agnieszka (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
The article describes the development of Polish avant-garde theater in the 50s, 60s and 70s of the 20th century. The major artistic trends in theatrical art this period were discussed. Leszek Mądzika’s theater was presented as a natural continuation and culmination of many theoretical ideas and explorations of artistic experimenters of this period. This article discusses the exploration of the theater authors of the described epoch which in a very expressive way were focussed in the plastic form of the Leszek Mądzik theater.